MUTATION AND PROMOTION SYSTEM AND ITS RELATION TO EMPLOYEESATISFACTION AND JOB PERFORMANCE OF WEST KALIMANTAN IMMIGRATION OFFICE - Rinaldi, Udin; Sani, Sani; Martono, Martono (Jurnal Aplikasi Manajemen, 2018)
the purpose of this study is to investigate mutation and promotion system and its relation to employeesatisfaction and jobperformance of West Kalimantan Immigration Office.This study used descriptive qualitative research approach with Explanatory Research. 50 people were taken as sampleusing judgmental sampling method only to employees who have been transferred. Data was collected through questionnaires and analyzed using path analysis model. The results of this research answer the hypotheses: there is a significant influence of mutation on job satisfaction; there is a significant influence of promotion on job satisfaction; there is a significant influence of mutation on job performance;there is a significant influence of promotion on job performance, and there is a significant effect of job satisfaction on job performance. The datadiversity was explained using path analysis model of 62.2%, while the rest was explained by other variables not included in the model and error.